2020
DOI: 10.1093/ije/dyaa105
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood growth trajectory and later cognitive ability: evidence from a large prospective birth cohort of healthy term-born children

Abstract: Background Most studies of associations between child growth and cognitive ability were based on size at one or two ages and a single measure of cognition. We aimed to characterize different aspects of early growth and their associations with cognitive outcomes in childhood through adolescence. Methods In a sample of 12 368 Belarusian children born at term, we examined associations of length/height and weight trajectories ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The weight-to-length measurement is widely used to evaluate the growth status in children and was related to cognitive performance in adolescence . Therefore, the weight-to-tail length ratio was validated as an indicator of the rat growth status.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight-to-length measurement is widely used to evaluate the growth status in children and was related to cognitive performance in adolescence . Therefore, the weight-to-tail length ratio was validated as an indicator of the rat growth status.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The weight-to-length measurement is widely used to evaluate the growth status in children and was related to cognitive performance in adolescence. 21 Therefore, the weight-to-tail length ratio was validated as an indicator of the rat growth status. After 6 weeks, rats fed MBPD exhibited a significantly increased body weight and tail length compared to those fed diets supplemented with 7% protein (Figure 1a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Honolulu–Asia Aging Study suggested that height in middle life was a marker of childhood growth and was associated with dementia and cognitive impairment among elderly Japanese–American men living in Hawaii [ 7 ]. In a large Belarusian prospective birth cohort study, a taller height between birth and age 6.5 years was associated with higher cognitive scores at age 16 years, with a 2.5-point (95% CI 1.9, 3.0) per standard deviation increase [ 21 ]. Most studies in Western countries have suggested that height is associated with cognitive function in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Cognition refers to the process in which individuals extract, process, and store information ( Bayne et al, 2019 ). It is the representation of the interconnection and interaction between objective things ( Ahmed et al, 2020 ). Cognition usually includes perception, attention, memory, thinking, and imagination ( Shao, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, children and adolescents are the golden age of cognitive development. The level of cognitive development at this stage is of great significance to individual academic performance, mental health, and social development in adulthood ( Blakemore and Choudhury, 2006 ; Ahmed et al, 2020 ). For example, fluid intelligence and executive function are closely related to the academic performance and acquired achievement of children and adolescents ( Graham et al, 2017 ; Tikhomirova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%